REFORMULASI TINDAK PIDANA PENGHINAAN PRESIDEN DALAM RKUHP SEBAGAI JALAN TENGAH PENEGAKAN HUKUM PIDANA INDONESIA (Lex Jurnalica, 2022)
Reformulation The criminal act of insulting the President in the Draff Criminal Law has raised pros and cons in the community. Many view that this reformulation is a form of silencing freedom of expression, but on the other hand there are also those who view that this reformulation is a form of protecting the dignity of the President and Vice President as heads of state and heads of government. The research method used is juridical normative based on legal science which examines the regulation of criminal acts of insulting the President in positive law and conducts comparative studies with other countries. So that the problem in this paper is how to formulate the criminal act of insulting the president in Indonesian positive law and how to reformulate the criminal act of insulting the president in reforming Indonesian criminal law. Based on the results of the study that the concept of humiliation in the Draff Criminal Law is a middle way, on the one hand, it still provides protection for the President's Personal as the head of state who has a strategic position and on the other hand to avoid the arbitrariness of law enforcement officials so that the offense of insulting the President in the Draf Criminal Law is shifted into a complaint offense